Identifying and Using CGIAR's Comparative Advantage - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2022)
Comparative Advantage (CA) is one of the most powerful theoretical insights in economics. It provides a useful framework for identifying areas where CGIAR's efforts are most crucial to achieving its mission - to deliver science and innovation that advance the transformation of food, land, and water systems in a climate crisis. 'One CGIAR' transition facilitates and promotes the use of portfolio approaches to research and innovation. In that context, ISDC aims to put the concept of CA to effective use in research portfolio management at all levels of the System. Applying a CA analysis can produce a more streamlined, purposive, and intentional research portfolio. It is designed to harness the various competencies of CGIAR entities, and other organizations with which the system interacts, to make the 'sum of its parts' as large as possible. This Technical Note first introduces the CA concept, its aims and benefits, and illustrates how gain from specialization occurs. Then, it reflects on possible sources of CA, and how broad categories (i.e., incentives, human capital, biophysical capital (such as labs, genetic material, and equipment), and social capital) can help identifying outputs in which CGIAR is likely to have CA. The four key steps of a CA analysis are then described, and retrospectively applied to specific deliverables from the Livestock Genetics Flagship of the CGIAR Research Program on Livestock. The final section summarizes these insights.